Meritev sedežnih pritiskov pri osebah z okvaro hrbtenjače kot metoda za pomoč pri izbiri ustrezne antidekubitusne sedežne blazine - Grabner, Petra (Rehabilitacija (Ljubljana), 2014)
Introduction: Pressure ulcers are a frequent complication in acute as well as chronic stage after a spinal cord lesion. The risk of forming a pressure ulcer can be lowered by using a seat cushion. The method of measuring seating pressure can be of help in choosing an appropriate seat cushion. At the Department for Rehabilitation of Patients After Spinal Cord Injury in Ljubljana, we started using the method in 2010. The aim of reviewing all the performed measurements was to suggest a protocol of choosing patients and performing the assessment of seating pressure. Methods: We reviewed the literature about measuring seating pressure in persons with spinal cord lesion and all the measurements taken at our Department since the start of using the method. Results: In four years, we assessed 46 patients (36 men, 10 women). Most of them (27) had a lesion of the thoracic or lumbar spinal cord, 19 had a cervical spinal cord lesion. The measurement of seating pressure was performed more frequently in the outpatient clinic than in hospitalised patients. We tested at least two different seat cushions. Conclusion: Measuring seating pressure has an important role in testing a seat cushion, but cannot be the only criterion for selecting an appropriate cushion. The method could be used more often and for this purpose we need to make a protocol with inclusion criteria and defined guidelines for seating pressure assessment.
Keywords: meritev sedežnih pritiskov; okvara hrbtenjače; Pressure Ulcer; razjeda zaradi pritiska; seat cushion; seating pressure; seating pressure measurement; sedežna blazina; sedežni pritiski; Spinal Cord Compression; spinal cord lesion